Rethinking open government as innovation for inclusive development: Open access, data and ICT in South Africa. Issue 3 (16th April 2021) - Plantinga, Paul; Adams, Rachel
Abstract : Open government has come to be closely associated with innovation for inclusive development (IID). These two areas of practice and research have converged around similar mechanisms aimed at achieving inclusive development outcomes including: open interaction between government, technologists and end-users in the design of policies and services; open, market-oriented approaches to delivering public services and meeting the needs of citizens; and a central role for information and communication technologies (ICTs) in policy development and innovation activities. We argue, however, that an uncritical adoption of open, ICT-oriented practices risks shifting responsibility and trust for governance and development outcomes to largely unaccountable global and national network enterprises. Taking South Africa as our primary focus, including its new White Paper on Science, Technology and Innovation (STI), we note a renewed interest in adopting open government practices in relation to IID. More significant, we suggest, is the emergence of 'grassroots', hybrid civic-technology innovation networks at the fringes of formal open government initiatives. This article considers new questions that arise around how these grassroots movements sustain meaningful interaction with mainstream STI processes, how public officials may engage with such movements in order to meet national development outcomes, and the role of ICT in these spaces.